The effect of using the Kolb model (assimilation pattern - divergent pattern) in developing the accuracy of performance of the skills of handling and scoring for football for the youth players of Naft Maysan Sports Club - Qasim Kadhim AL-Shareefi, Maytham (International Journal of Psychosocial Rehabilitation, 2020)
The continuous search for everything that develops the work of coaches in order to obtain the best achievements during the competitions that are held locally, continually, and internationally is the search for modern and effective methods, including Kolb's sample in learning as it depends on scientific dimensions related to steps. Educational assistance to the learner or trainee to move from one level to a higher level according to these regular steps, as well as to identify the learner’s level of mind and choose the level that suits him in learning through a scale prepared for this purpose. Here, the importance of research can be identified.The research problem, the method of work or the one method, whether it is education or training, and the method that does not take into account the nature of the player's growth and his mental and physical characteristics is a problem that must be addressed, so the researcher resorted to using the Kolb sample as a model that depends on the extent of the scientific excitement that the player moves during the learning stages Through experiments based on abstract steps to concrete, passing through the contemplation stage and ending the experiment according to the previously prepared plan by the teacher or trainer. The aim of the research is to identify the effect of using the Kolb sample with two growths (interstitial stiffness) in developing the accurate performance of the handling and scoring skills of the players of Al Shabab Oil Club in Maysan football, as well as identifying the differences. The morale between the research groups in the pre-tests and the dimensions, as well as the identification of the ethical differences between those groups in the dimensional tests, and the influencer hypothesized that there is an effect of using the Kolb sample with two growths (a sympathetic stutter) in developing the accurate performance of the handling and scoring skills of the players of the Maysan Youth Club in football. In addition to all, there are statistically significant differences between the pre-tests and the three-dimensional search groups for the hand and in the hand dimension tests again. The researcher used the method of demonstrating its suitability, research procedures, and the sample of searching for youth club Zait Maysan football players for ages ranging from 14 to 16 years, divided into three groups. The officer initially adopts homogeneity and parity between the members of the three groups, and the three groups are prepared and are 18 players, 6 players for each group, divided between groups by the method of drawing lots. In addition, a scale was adopted based on determining the training method preferred by the player, which was divided into Kan. After the pre-tests, the education program wm was applied by conducting dimensional tests and statistical treatments to find out which of them the results of the research represented the existence of statistically significant differences between the tests of tribal groups and the three dimensions Which was searched for and the subsequent tests, either in the subsequent tests, it was noted that the results outweigh the total Tin demo Tin over the control group, as well as the first experimental group (Astepa) over the second experimental group (interstitial) in those tests.